POTENSI WILAYAH DAN DAMPAK SERTA KONTRIBUSI KOMODITAS TEMBAKAU BESUKI NA-OOGST TANAM AWAL TERHADAP SEKTOR PERKEBUNAN KABUPATEN JEMBER - Purnamasari, Ari Putri; Santoso, Kabul; Januar, Jani (Jurnal Sosial Ekonomi Pertanian, 2014)
Regional development of basis commodity needs refer to regional analysis. The regional analysis will provide directions on how far a commodity has base strength in supporting economics activities, especially the contribution to plantation sector. This research was purposively conducted in Jember Regency. The phenomena discussed were whether the region on the basis of tobacco Besuki Na-Oogst commodity of Early Planting (Bes-NOTA) in its distribution followed specialization and locality principles, how the commodity distribution characteristics were, and how the impacts and contributions toward economic development of plantation sector. The research used descriptive and analytical methods aided with analyses of Location Quotient (LQ), Specialization (Sp) and Localization (Lp). The research conclude that: (1) Base regional potentials of Bes-NOTA tobacco in accordance with the indicators of land (ha) and production (tonnes) area in Jember Regency were located in Sub-Districts of Tempurejo, Balung, Ambulu, Wuluhan, Rambipuji, Jenggawah, Ajung, and Puger, (2)The impacts Bes-NOTA tobacco commodity to the region economy which were analysed using basic service ratio, regional multiplier, short multiplier and long multiplier showed that the business of Bes-NOTA tobacco commodity in Jember Regency in general provided positive impacts that could support the performance of plantation sector in Jember Regency, and (3) Average contribution given by Bes-NOTA tobacco commodity sector during 2002-2011 was 4,43%. Â Keywords: Location quotient, impacts, and contribution of Early Planted Besuki Na-Oogst tobacco